Low Birthweight Infant Feeding Practices and Growth Patterns in the First Six Months of Life in Resource-Limited Settings. (14th June 2022) - Vesel, Linda; Kisenge, Rodrick; Koujalagi, Murugaraj; Kusagur, Varun; Manji, Karim; Mvalo, Tisungane; Nayak, Rashmita; Phiri, Melda; Saidi, Friday; Semrau, Katherine; Sudfeld, Christopher
Abstract: Objectives: The Low Birthweight Infant Feeding Exploration (LIFE) study addresses the increased risk for mortality and poor health outcomes as well as the paucity of evidence on feeding and growth among low birthweight (LBW) infants in limited-resource settings. The objectives were to describe the feeding profile of low birthweight (LBW, < 2.5kg) infants in the first half of infancy; and to examine growth patterns and early risk factors of poor growth outcomes at six months. Methods: The LIFE study was a formative, multi-site, observational cohort study. Data were collected during eight visits from birth to six months for more than 1100 moderately LBW infants recruited from 12 health facilities in four sites in India, Malawi and Tanzania. Results: A total of 1114 infants and their mothers were enrolled in the observational study comprising19% preterm small-for-gestational age (SGA), 26% preterm appropriate-for-gestational age (AGA) and 55% term SGA infants with significant differences in prevalence of birth phenotypes by region. More than 90% of infants were fed breastmilk at each visit before six months; only 42% were exclusively breastfed up to six months. Among the pooled sample of LBW infants, 14% did not regain their birthweight by two weeks; and 33%, 26% and 10% were stunted, underweight and wasted at six months, respectively. Preterm-SGA infants [1.76 (p = 0.001) and 1.80 (p = 0.012)] and term-SGA infants [2.44 (p < 0.001) and 2.82 (p = 0.012)] had significantly greater risks for stunting and wasting at six months than preterm-AGA infants. There was no significant difference in the risk for underweight between the phenotypes. Infants not regaining birthweight by two weeks had 1.48 (p = 0.002) and 1.52 (p = 0.005) times greater risk for stunting and underweight at six months, respectively. There was no relationship between lack of birthweight regain by two weeks and wasting at six months. Finally, there was no relationship between exclusive breastfeeding up to six months and growth outcomes at 6 months. Conclusions: LBW infants are a heterogenous group. Birth outcomes and very early growth matter and should be prioritized in efforts to prevent growth failure and allocate scarce resources. Poor growth outcomes can be prevented with focused, proactive interventions at key timepoints. Funding Sources: Bill & Melinda Gates Foundation.